A Through-Space Charge Transfer Mechanism for Explaining the Oxidation of 2-Chlorophenol on a Tetrasulphonated Nickel(Iii) Phthalocyanine - Cardenas-Jiron, G; Cortes-Arriagada, D (Elsevier B.V., 2011)
In this work a mechanism is proposed to explain the oxidation of 2-chlorophenol (2-CP) mediated by a tetrasulphonated nickel(III) phthalocyanine (NiTSPc) in the gas phase with the density functional and wavefunction theories. Two hybrid density functionals (B3LYP, MPWB1K) in their unrestricted and restricted open form, and the unrestricted semiempirical Hartree-Fock PM3 method (UHF PM3) were applied. Using a supermolecule scheme (2-CP•••Ni(III)TSPc) and a reaction coordinate (rNi•••O) denoted by the distance between Ni and O (2-CP), for the rNi•••O = 3.6-5.4 Å range we found that both functionals in their unrestricted and restricted open form showed a charge transfer (CT) of about 0.8-0.9 electrons from 2-CP towards NiTSPc, as obtained by the spin density and the Mulliken electronic population change. Similar results were obtained for UHF PM3 (one electron CT). Thus, our results showed that the oxidation of 2-chlorophenol follows a through-space mechanism. Calculations of the interaction energy carried out for the 2-CP•••Ni(III)TSPc supermolecule showed a trend towards the formation of a potential well for the rNi···O = 3.8-5.0 Å region which was more apparent for the unrestricted methods (UB3LYP, UMPWB1K, UHF PM3). The energy minimum was obtained in the range 4.2-4.6 Å. However, in contrast with the PM3 results, we found that the density functionals used do not predict negative values for the interaction energy, confirming that in this case they fail to describe this kind of non-covalent interactions. © 2010 Elsevier B.V.